Characterization of the Hoxd4 neural enhancer - Ler, Ser Yeng (2012)
Hox genes encode homeodomain-containing transcription factors, required for correct antero-posterior patterning. In mammals, there are 39 Hox genes, distributed over four clusters, named A-D, and they are subdivided into thirteen paralogs. The main project objective is to understand Hox gene regulation through the study of Hoxd4 neural enhancer(s).